Globalization, internationalization and education reforms in Russia. Russian-Vietnamese relations in education - Kraevskaia, Natalia (Đại học Quốc gia Hà Nội, 2020)
The paper analyzes some of contradictions in university education caused by the rapid integration of Russian traditional national education into Euro-American system. Overcoming certain obstacles for reform, Russian higher education’s internationalization continues to develop and to strengthen. Following the world trends of internationalisation of high education, Russian education has integrated into the metaprograms of international cooperation. Attracting foreign students to national university is also one of the main component of internationalization along with export of education and appropriation of international knowledge. The relationship between Vietnam and Russian has been firmly establised since 1950s. In the new context of internationalisation in education, this strategic relation has entered a new phase with the concern and interest from both sides.